Education Transformation in the Era of Digital Disruption 4.0 - Sandy Kosasi (JUDIMAS, 2020)
In the digital era of disruption 4.0, featured automatization and connectivitation movement of transformation on education and work competencies were not linear anymore, where every graduate student must master the skills of digital literature, technology, and human resource. The social community service seminar was followed by 66 candidates consist of students, teachers, and structural officials on SMK Negeri 2 Singkawang. The seminar was an open lecturer discussion, question, and answer methods. The seminar emphasized the necessity to build virtual classrooms for teachers and students to collaborate internally or between schools by exchanging information, knowledge, and learning together in increasing their competencies.